The Effect of Credit Risk and Bank Size on Bank Profitability in Indonesia Before and During the Covid-19 Pandemic - Fenti Utari; Viverita Viverita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study empirically examines the effect of credit risk using a new measure that is influenced by stimulus policy in Indonesia and bank size on the profitability of Indonesian banks during the Covid-19 pandemic. It employed the Generalized Method of Moments (GMM) Dynamic Model to obtain an overview of the effectiveness of the relaxation policy in maintaining the profitability of Indonesian banks. The stimulus policy by the regulator during the COVID-19 pandemic changed the credit risk calculation and this research contributed by using credit risk measurement adjusted to the stimulus policy by adding restructuring loans in current quality. The study found that credit risk negatively affected profitability in the period during the Covid-19 pandemic. This finding is probably due to the stimulus policy allowing banks to remain current on the credit quality with no addition to the provision. Bank profitability during the pandemic was not significantly affected by credit risk, allegedly among others, also influenced by the good adaptability of banks in Indonesia through additional services. Bank size has had a significant negative effect on profitability during the COVID-19 pandemic for small, medium, and large banks. The larger the size of the bank, the riskier it becomes due to the addition of reputation management including other operational costs.